Bone morphogenic protein 6: a member of a novel class of prognostic factors expressed by normal and malignant plasma cells inhibiting proliferation and angiogenesis - Seckinger, Anja; Meißner, Tobias; Moreaux, J.; Goldschmidt, Hartmut; Fuhler, G. M.; Benner, Axel; Hundemer, Michael; Rème, T.; Shaughnessy, J. D.; Barlogie, B.; Bertsch, Uta; Hillengaß, Jens; et al. (Oncogene, 2009)
Pathogenesis of multiple myeloma is associated with an aberrant expression of pro-proliferative, pro-angiogenic and bone-metabolism-modifying factors by malignant plasma cells. Given the frequently long time span from diagnosis of early-stage plasma cell dyscrasias to overt myeloma and the mostly low proliferation rate of malignant plasma cells, we hypothesize these to similarly express a novel class of inhibitory factors of potential prognostic relevance. Bone morphogenic proteins (BMPs) represent possible candidates as they inhibit proliferation, stimulate bone formation and have an effect on the survival of cancer patients. We assessed the expression of BMPs and their receptors by Affymetrix DNA microarrays (n=779) including CD138-purified primary myeloma cell samples (n=635) of previously untreated patients. BMP6 is the only BMP expressed by malignant and normal plasma cells. Its expression is significantly lower in proliferating myeloma cells, myeloma cell lines or plasmablasts. BMP6 significantly inhibits the proliferation of myeloma cell lines, survival of primary myeloma cells and in vitro angiogenesis. A high BMP6 expression in primary myeloma cell samples delineates significantly superior overall survival for patients undergoing high-dose chemotherapy independent of conventional prognostic factors (International Staging System (ISS) stage, β2 microglobulin).
Gesehen am 12.01.2022